Factors Associated With Mental Suffering in the Brazilian Population: A Multilevel Analysis - Bezerra, Héllyda de Souza; Alves, Roberta Machado; Souza, Talita Araujo de; Medeiros, Arthur de Almeida; Barbosa, Isabelle Ribeiro (Frontiers in Psychology, 2021)
Purpose: to analyze how individual characteristics and the social context are associated with mental distress symptoms in the Brazilian population. Method: a multilevel cross-sectional study with data from the 2013 National Health Survey. There were two dependent variables: a) decreased vital energy and somatic symptoms, b) the presence of depressive thoughts. The independent variables were biological characteristics, education and income, habits and lifestyle, and context variables. Bivariate analysis was performed, and Prevalence Ratios calculated in a Poisson Regression (95% CI). A multilevel Poisson Regression was performed to verify the effect of individual and contextual variables. Results: regarding depressive thoughts, young and middle-aged individuals, low education, women, absence of partner, smokers or former smokers, and absence of health insurance were the categories at highest risk; belonging to classes D-E and living in states with lower expected years of schooling proved to be protective factors. Similar results were found for the second outcome. Conclusions: symptoms of mental distress were associated with the individual characteristics and contextual aspects of the federation unit. These findings indicate the importance of strengthening psychosocial care aimed at vulnerable groups.